An Ethnographic Review on the Reception of Sangir Community in Solok Selatan to Giving Alms - Syafruddin, Syafruddin; Hasan, Nursalman (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
This article describes the date of the existence of an economic pillar in a community or ethnic group that is part of the culture in welfare. The economic pillars are zakat, infaq, and sadaqah (alms). In its development, it has its own existence and different practices, such as that of the Sangir community, which understands alms to be true, giving, and appreciating. Forms of practice such as; first, on normal days which can be seen from the number of weekly receipts of the Sangir mosque which reaches millions of rupiah, secondly on major Islamic holidays such as Ramadan and Eid al-Adha, and thirdly at certain moments such as the Malapeh tradition which is carried out during the hundred days and julo-julo custom at the time of walimah. The existence and persistence of this cannot be separated from the knowledge possessed by the Sangir community, as well as the role of religious and traditional leaders in cultural settings. The variety of alms receptions that have become part of the pattern of people's lives certainly has an influence, both on the environment and for the ethnic community itself.